Slow Freezing vs. Vitrification of Testicular Tissue in Nontraditional Animal Models - Sandoval, Eluzai Dinai Pinto [UNESP]; Lee, Pei-Chih; Duarte, José Mauricio Barbanti [UNESP]; Comizzoli, Pierre (SAGE Publications, 2025)
Introduction: Optimal cryopreservation of testicular tissue is essential for species research and conservation, enabling long-term storage of genetic resources through vitrification or slow freezing. Comparing responses from different taxonomic groups to these techniques is crucial for refining protocols and improving cryopreservation outcomes. Objectives: This study evaluated the effects of cryopreservation on cell viability, morphology, mitochondrial activity, and proliferative potential to optimize testicular tissue preservation strategies for wildlife conservation. Methods: We assessed testicular tissue from Felidae and Cervidae, including domestic cats (Felis catus) and Neotropical deer species, white-tailed deer (Odocoileus virginianus), Brazilian red brocket deer (Mazama nana), and gray brocket deer (Subulo gouazoubira). Experimental groups included control (no cryopreservation), slow freezing using Mr. Frosty or progressive temperature decrease, and conventional vitrification. Results: All methods preserved live cells and normal tissue morphology; however, compared with fresh tissue, cryopreservation significantly reduced tissue viability, mitochondrial membrane potential, and the proportion of intact seminiferous tubules. Species-specific differences emerged, with vitrification being most effective for domestic cats, while slow freezing yielded better results for Neotropical deer. Despite lower viability scores, vitrification could still be an acceptable option for cervids due to its rapid processing and minimal equipment requirements. In addition, post-cryopreservation tissue culture increased cell abnormalities, highlighting the need to optimize culture conditions for different species. Conclusion: This comparative study advances reproductive tissue preservation techniques and emphasizes the importance of tailored cryopreservation as well as in vitro culture protocols for diverse taxonomic groups.